Histone acetyltransferase CSRP2BP promotes the epithelial–mesenchymal transition and metastasis of cervical cancer cells by activating N-cadherin - Xiaohui Yang; Fei Sun; Yueying Gao; MengYongwei Li; Mian Liu; Yunjian Wei; Qiuling Jie; Yibing Wang; Jiaoqi Mei; Jingjing Mei; Linna Ma; Yuechuan Shi; et al. (Journal of Experimental & Clinical Cancer Research, 2023)
Abstract Background Dysregulated epithelial–mesenchymal transition (EMT) is involved in cervical cancer metastasis and associated with histone acetylation. However, the underlying molecular mechanisms of histone acetylation in cervical cancer EMT and metastasis are still elusive. Methods We systematically investigated the expression patterns of histone acetylation genes and their correlations with the EMT pathway in cervical cancer. The expression of CSRP2BP among cervical cancer tissues and cell lines was detected using Western blotting and immunohistochemistry analyses. The effects of CSRP2BP on cervical cancer cell proliferation and tumorigenicity were examined by cell growth curve, EdU assay, flow cytometry and xenotransplantation assays. Wound healing assays, transwell migration assays and pulmonary metastasis model were used to evaluate the effects of CSRP2BP on cell invasion and metastasis of cervical cancer cells in vivo and in vitro. RNA-seq, chromatin immunoprecipitation (ChIP), co-immunoprecipitation (Co-IP) and luciferase reporter assays were used to uncover the molecular mechanisms of CSRP2BP in promoting cervical cancer EMT and metastasis. Results We prioritized a top candidate histone acetyltransferase, CSRP2BP, as a key player in cervical cancer EMT and metastasis. The expression of CSRP2BP was significantly increased in cervical cancer tissues and high CSRP2BP expression was associated with poor prognosis. Overexpression of CSRP2BP promoted cervical cancer cell proliferation and metastasis both in vitro and in vivo, while knockdown of CSRP2BP obtained the opposite effects. In addition, CSRP2BP promoted resistance to cisplatin chemotherapy. Mechanistically, CSRP2BP mediated histone 4 acetylation at lysine sites 5 and 12, cooperated with the transcription factor SMAD4 to bind to the SEB2 sequence in the N-cadherin gene promotor and upregulated N-cadherin transcription. Consequently, CSRP2BP promoted cervical cancer cell EMT and metastasis through activating N-cadherin. Conclusions This study demonstrates that the histone acetyltransferase CSRP2BP promotes cervical cancer metastasis partially through increasing the EMT and suggests that CSRP2BP could be a prognostic marker and a potential therapeutic target for combating cervical cancer metastasis.